Performance of Metagenomic Next-Generation Sequencing for the Diagnosis of Cryptococcal Meningitis in HIV-Negative Patients - Gan, Zhouqing; Liu, Jia; Wang, Yijie; Yang, Lu; Lou, Zheng; Xia, Han; Li, Min; Chen, Zhuolin; Jiang, Ying; Peng, Fuhua (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives Metagenomic next-generation sequencing (mNGS) has been applied more and more widely for the diagnosis of infectious diseases, but its performance in the diagnosis of cryptococcal meningitis (CM) remains unclear. Methods Cerebrospinal fluid (CSF) samples from 197 HIV-negative patients with suspected central nervous system infections were tested simultaneously by mNGS and routine methods [India ink staining, fungal culture, or cryptococcal antigen (CrAg) tests]. The performance of mNGS was evaluated. Results Of the 197 enrolled cases, 46 (23.4%) cases were finally diagnosed with CM, including 43 (93.5%) Cryptococcus neoformans infections and 3 (6.5%) Cryptococcus gattii infections. The sensitivity, specificity, positive predictive value, negative predictive value, and concordance rate of mNGS were 93.5% [95% confidence interval (CI) at 86.4%~100.0%], 96.0% (95% CI at 92.9%~99.1%), 87.8%, 98.0%, and 95.4%, respectively. Comparing to the conventional diagnostic methods, the sensitivity and concordance rate of mNGS were slightly lower than those of CrAg tests (97.4%) but higher than those of India ink (63.0%) and culture (76.7%). Besides, mNGS had a sensitivity of 100.0% against culture. It should be noted that mNGS could identify Cryptococcus at species level; C. gattii of the 3 cases was only distinguished by mNGS. Conclusions CSF mNGS can be considered as a supplementary test to diagnose CM and directly distinguish C. gattii from C. neoformans in clinical specimens.